Comparative Analysis Of The Works "Tristan And Isolde" And "Iliada" - Akbaraliyeva, Khurshida (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2026)
This article comparatively studies two great works of world literature - the medieval European epic "Tristan and Isolde" and the ancient Greek epic "Iliad". The plot of the works, the system of artistic images, the interpretation of the themes of war and love, and universal values ​​are compared. As a result of the study, the similarities and differences of heroism, tragedy, and human feelings in both works are identified.